2015
DOI: 10.1111/jopr.12392
|View full text |Cite
|
Sign up to set email alerts
|

Can Impression Procedures Affect Certain Vital Functions of Edentulous Patients? A Clinical Study

Abstract: According to the results of this clinical study, the impression procedures may affect the PR values and lead to desaturation events in edentulous patients; however, further studies evaluating blood gas levels, which indicate precise AOS values, are necessary to support the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It should be noted that the current study investigated the two aspects of this problem. When blood pressure, pulse rate, and pulse pressure were analyzed without sex separation, the difference was not significant before and after dental impression (15). But, when the sex groups were separately analyzed, it was found that unlike other variables, pulse pressure difference was statistically significant before and after dental impression in women.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It should be noted that the current study investigated the two aspects of this problem. When blood pressure, pulse rate, and pulse pressure were analyzed without sex separation, the difference was not significant before and after dental impression (15). But, when the sex groups were separately analyzed, it was found that unlike other variables, pulse pressure difference was statistically significant before and after dental impression in women.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, complex medical equipment is required that is not normally found in a dental office. Thus, this study was designed to evaluate parasympathetic effects on the cardiovascular system by measuring available indicators (15). Some studies have concluded that usual dental procedures could not induce significant changes in blood pressure whereas some others have reported that local anesthesia can lead to elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%